Sharia Compensation Schemes and Employee Performance in Contemporary Islamic Economics - Heru Subiyantoro; Karnaji; Fendy Suhariadi (Faculty of Sharia, IAIN Metro, 2025)
This study investigates the role of Sharia-compliant compensation schemes in optimizing employee performance through a qualitative approach. Within the framework of contemporary Islamic economics, compensation is not only regarded as a financial reward but also as an instrument of justice, blessing, and adherence to Sharia principles. Sharia-based compensation highlights the ethical and moral dimensions of employee welfare by emphasizing material and spiritual aspects. The study underscores the mediating role of job satisfaction and the moderating influence of religious motivation in strengthening the relationship between compensation schemes and employee performance. Data were collected through in-depth interviews and participatory observations conducted at Sharia-based institutions and companies in Indonesia, ensuring contextual depth and reliability of the findings. Thematic analysis indicates that compensation aligned with Sharia values can significantly enhance employee loyalty, strengthen work ethic, and increase overall productivity. Furthermore, the spiritual dimension of compensation is essential in cultivating intrinsic motivation, particularly when supported by an ethical and religious work environment. Integrating material and non-material values creates a more holistic approach to human resource management. The findings suggest that a comprehensive Sharia compensation system has far-reaching implications, as it addresses employees’ financial well-being and contributes to their overall spiritual and psychological welfare. The study concludes by emphasizing the importance of developing HR management strategies rooted in Islamic values as a sustainable and effective pathway to improving employee performance and organizational resilience.